Leach testing of bayer residue products in various environments - Attiwell, Shelly Eileen (Curtin University, 2013)
Two bauxite residue products, Alkaloam® and Red Lime™, generated from Alcoa of Australia’s Western Australia alumina refineries, have the potential to be re-used in a range of applications, in particular in agricultural land management as soil amendments for phosphorus retention and as an agricultural liming agent.Currently there are no regulatory frameworks or guidelines in Western Australia to promote and facilitate the re-use of industrial by-products. This is partly due to the lack of assessment protocols required to ensure that all regulatory standards have been met, with assurance that a by-product is safe and acceptable by the community as a suitable raw material for re-use. In addition, the Australian Standard Leaching Procedure (ASLP), the standard leach test adopted in Australia for environmental assessments, is significantly limited and not suitable for assessing leaching in industrial by-products, such as Alkaloam® and Red Lime™.The aim of this thesis was therefore to determine whether a more suitable leach test could be used as an alternative to ASLP for assessing industrial by-products and apply this leach test to Alkaloam® and Red Lime™ for investigating their leach behaviour when used as a soil amendment or liming agent.This thesis reported on relevant literature on the re-use of bauxite residue products, international leach test procedures and current assessment of industrial by-products for re-use.The European standard pH dependent leach test was compared to ASLP for assessing the leaching behaviour of Alkaloam® and Red Lime™ and for determining its suitability for assessing industrial by-products for re-use in different pH scenarios. This leach test was more superior to ASLP in that it provided more accurate and fundamental leaching information on Alkaloam® and Red Lime™ and was considered more suitable for assessing by-products for re-use, in particular materials that were highly alkaline and exhibited high buffering capacity.Method optimisation was conducted on the pH dependent leach test to improve leaching assessments on clay type soils and to allow nitrate leaching to be assessed in WA soils ameliorated with Alkaloam® and Red Lime.The main focus of this thesis was on characterising and assessing the pH dependent leaching behaviour of Alkaloam® and Red Lime™ and determining changes in leaching at different pH for a range of WA soils, when ameliorated with Alkaloam® and Red Lime™ at an application rate of 6.25g/kg (Alkaloam®) and 1.6g/kg (Red Lime™). A Bassendean soil and agricultural soils in the Peel Harvey catchment and Merredin and Newdegate region were assessed in this study. LeachXS™ geochemical modelling was applied to the pH dependent leach data to identify the processes controlling leaching of species in these scenarios as well as the speciation likely to be present in the liquid and solid phase during leaching.It is anticipated that this information will be a key input into the environmental assessment of Alkaloam® and Red Lime™ as an agricultural soil ameliorant and liming agent as these products progress towards becoming commercialised as raw material commodities.